Industry Partners’ Feedback on Students’ On-The-Job Training: Basis for Curriculum Enhancement and Intervention - Bentor, Claire Theresa S.; Sabonsolin, John Cavin M.; Niez, Roland A. (Future Science / FSH-PH Publications, 2022)
Training effectiveness is measured by observable changes in knowledge, skills, and attitude after training has been conducted. This study investigates the industry partners' feedback on the On-the-Job training of the Bachelor of Arts in Communication and Bachelor of Arts in Economics interns. The researchers utilized the mixed method approach using the embedded research design. The researchers used the retrospective -descriptive quantitative design for the quantitative data. 40 practicum students' performances were evaluated during their on-the-job training for the School Year 2019 – 2020. Data were analyzed and presented using statistic numerical measures, and the relationship of variables was tested using spearman's rank-order correlation coefficient at a 0.05 significant value. Moreover, the researchers used thematic analysis of Braun and Clarke (2006) for the qualitative data. Results show that there is enough evidence to suggest that there is no statistically significant correlation between the profile of the students and their performance in practicum at α=0.05. Based on these findings, it is inferred that the students’ sex and course have no bearing on their shown knowledge and attitude, punctuality and active presence, performance proficiencies, and interpersonal interactions abilities at work. It is also found out that the industry partners noted strengths and weaknesses to the practicum students. This study discovered that the industry partner perceived the practicum students' performance to be competent in actual practice. Additionally, these findings pave way for the Economics and Communication department to select, develop, arrange, and implement meaningful classroom activities that promote sociability and prepare students for future careers.